Peran Terminal Petikemas Dalam Meningkatkan Daya Saing Dan Efisiensi Logistik Maritim Indonesia - triningsih, novia (Peneliti.net, 2024)
This research discusses the role of container terminals in the context of increasing the competitiveness and efficiency of maritime logistics in Indonesia. As an important maritime country, Indonesia views container terminals as a strategic element in improving connectivity and efficiency of its maritime logistics supply chain. This research aims to identify factors that influence the role of container terminals, including operational efficiency, application of technology, and cooperation in the supply chain. The research methodology uses qualitative methods with a descriptive analysis approach. Data was collected through surveys, interviews and document analysis from selected container terminals at major ports in Indonesia. Regression analysis, cluster analysis, and content analysis are used to understand the relationship between the independent variable (the role of container terminals) and the dependent variable (maritime logistics efficiency and competitiveness). This research provides understanding of how the role of container terminals can be optimized to increase the competitiveness and efficiency of maritime logistics in Indonesia. These findings have important implications for policy making, container terminal management, and future maritime logistics infrastructure development strategies.